2006
DOI: 10.1152/ajpcell.00520.2005
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-macrophage colony-stimulating factor increases l-arginine transport through the induction of CAT2 in bone marrow-derived macrophages

Abstract: L-arginine transport is crucial for macrophage activation because it supplies substrate for the key enzymes nitric oxide synthase 2 and arginase I. These enzymes participate in classic and alternative activation of macrophages, respectively. Classic activation of macrophages is induced by type I cytokines, and alternative activation is induced by type II cytokines. The granulocyte macrophage colony-stimulating factor (GM-CSF), in addition to inducing proliferation and differentiation of macrophages, activates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Similar results have been obtained in mouse peritoneal macrophages [19]. Moreover, while describing a case of a LPI subject, we have recently demonstrated that system y ϩ L activity is impaired in monocytes and AM but not in mesenchymal cells [20].…”
Section: Introductionsupporting
confidence: 87%
“…Similar results have been obtained in mouse peritoneal macrophages [19]. Moreover, while describing a case of a LPI subject, we have recently demonstrated that system y ϩ L activity is impaired in monocytes and AM but not in mesenchymal cells [20].…”
Section: Introductionsupporting
confidence: 87%
“…Nonetheless, infection with M. smegmatis (Ehrt et al, 1997), maturation in culture (Martin & Edwards, 1993), and specific experimental conditions may sufficiently increase reactive intermediate levels, especially for RNI, to have bactericidal action on this micro-organism, as suggested by our inhibition studies. Activation of the arginase pathway reduces arginine availability for the NO synthase reaction in murine macrophages (Martin et al, 2006). This leads to an increase in intracellular levels of Lglutamate.…”
Section: Discussionmentioning
confidence: 99%
“…The most relevant CAT member involved in MΦ functions is CAT-2, which can be expressed in two splice variants. CAT-2A is constitutively expressed in the liver and muscle cells [27], whereas the expression level CAT-2B is inducible in MΦs and strongly unregulated by IFN-γ, IFN-γ coupling with LPS, IL-4, and GM-CSF [28][29][30]. In the context of Leishmania infection, the expression and function of CAT-2B in MΦs are critical, because CAT-2B-mediated L-arginine transport potentially affects both iNOS and the arginase pathways.…”
Section: L-arginine Metabolism and Transport In Mammalian Cells Espementioning
confidence: 99%